Effects of gutting process on the shelf life of cultured meagre (Argyrosomus regius ASSO, 1801) stored at 4 ± 1 °C - BİLGİN,Şengül (2016)
Abstract The aim of this study was to determine chemical, nutritional and microbiological evaluation of whole or gutted meagre stored at 4 ± 1 oC. Whole ungutted (Group A), eviscerated (Group B), beheaded-eviscerated fish (Group C) and fillets (Group D) groups were created for this study. According to fatty acid analysis, it was determined that meagre is rich in PUFA content and the n3/n6 ratio is within the ideal limits. In all 4 groups, obtained from fillets values were the highest in general, quality parameters were found within acceptable limits. Psychrophilic and mesophilic aerobic bacteria counts exceeded the standards for fillet groups on 7th days of storage. According to microbiological analysis, ungutted, beheaded, eviscerated samples were not exceeded limit values on 9th day. In conclusion, whole or gutted (headed and eviscerated) storage of meagre is found to be more advantageous compared to fillets for storage at 4 ± 1 oC.